Chrome Analysis on Lichens at Ambient Air On Living Trees - Ashar Hasairin (Talenta Publisher, 2019)
The purpose of this study was to analyze the amount of chrome in lichens live on living tree Mahoni (Swietenia macrophylla) at ambien air in Pinang Baris Bus Station Medan. Purposive sampling method was conducted. The analitical data used was corelations product moment. Results showed 5 species of lichens were identified. Each the species contain Cr and Ocrolechia tartarea was the highest. Ambien weather at the atmosphere consists of NO2 22.21 µg/m3, SO2 16.29 µg/m3, CO 11 ppm, H2S 0,00883 ppm and O3 76.01 µg/m3. Temperatur 32.34 °C, relative humidity 69 %, light instensity 500 Joule and wind speed 2,1 m/s. Corelations chrome lichens to the ambien air showed result 0,15 is very low. Corelation lichens value to the ambien air is -0,13. Showed negatif and it is not significan and very low.